1997
DOI: 10.1007/bf01277664
|View full text |Cite
|
Sign up to set email alerts
|

Pergolide: treatment of choice in restless legs syndrome (RLS) and nocturnal myoclonus syndrome (NMS). A double-blind randomized crossover trial of pergolide versus L-Dopa

Abstract: A double-blind randomized crossover study of 0.125 mg Pergolide (Lilly) at bedtime versus 250mg L-Dopa + Carbidopa (Roche) was conducted in 16-day phases in 11 patients with idiopathic restless legs syndrome. Two patients reported a partial and 9 patients a complete relieve of motor restlessness while receiving Pergolide. Only 1 patient experienced an improvement of restlessness after L-Dopa. The patients showed polysomnographically a mean decrease in NMS cluster disturbed time by 45% from control on L-Dopa (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 20 publications
(22 reference statements)
1
32
0
1
Order By: Relevance
“…Placebo-controlled trials also demonstrate the efficacy of the DAs pramipexole [77], pergolide [78][79][80][81], bromocriptine [82], apomorphine [83], cabergoline [84], and rotigotine [84], and of the dopamine precursor levodopa [85][86][87]. Levodopa was inferior to pergolide in the only controlled comparative trial among dopaminergic medications [79].…”
Section: Treatment Of Restless Legs Syndromementioning
confidence: 97%
See 1 more Smart Citation
“…Placebo-controlled trials also demonstrate the efficacy of the DAs pramipexole [77], pergolide [78][79][80][81], bromocriptine [82], apomorphine [83], cabergoline [84], and rotigotine [84], and of the dopamine precursor levodopa [85][86][87]. Levodopa was inferior to pergolide in the only controlled comparative trial among dopaminergic medications [79].…”
Section: Treatment Of Restless Legs Syndromementioning
confidence: 97%
“…Levodopa was inferior to pergolide in the only controlled comparative trial among dopaminergic medications [79]. It is also felt to have greater potential for augmentation [88].…”
Section: Treatment Of Restless Legs Syndromementioning
confidence: 99%
“…Four of these trials are placebo-controlled mostly giving levodopa/DDCI as a single bedtime dose for nocturnal RLS symptoms [83][84][85]88]. Two trials, including an open study, have investigated the sustained release formulation of levodopa [87,89], while four trials have investigated levodopa compared to other agents such as pergolide [86], valproic acid [89], gabapentin [91], and cabergoline [90]. The dosages range between 100-300 mg per night as a single dose, with a second dose three hours after bedtime or in combination with a sustained-release formulation.…”
Section: ■ Levodopa/decarboxylase Inhibitor (Ddci)mentioning
confidence: 99%
“…Eight randomized controlled trials [83][84][85][86][87][88][89][90] are available to prove the efficacy of levodopa/DDCI in RLS therapy. Four of these trials are placebo-controlled mostly giving levodopa/DDCI as a single bedtime dose for nocturnal RLS symptoms [83][84][85]88].…”
Section: ■ Levodopa/decarboxylase Inhibitor (Ddci)mentioning
confidence: 99%
“…Most reports of benefit were observational with only a single small controlled study [77]. Pergolide was a second ergoline derivative that was found to be effective in 4 controlled studies that included up to 100 RLS patients [74], and was shown to be superior to levodopa in some studies [78]. Carbergoline is a long-acting ergoline derivative with an elimination half life of 65 h that has been evaluated in controlled studies and shown to be beneficial in RLS [79].…”
Section: Dopamine Agonists For Rlsmentioning
confidence: 99%